2017
DOI: 10.1002/jctb.5483
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic fructose removal from D‐psicose bioproduction model solution and the system modeling and simulation

Abstract: BACKGROUND The rare sugar D‐psicose has important physiological functions, and has been used as an ingredient in foods and dietary supplements. It can be mass produced from D‐fructose in industry. However, separation of D‐psicose from D‐fructose is difficult. RESULTS In this research, a reaction purification system consisting of two continuous stirred tank reactors (CSTR) containing immobilized glucose isomerase (GI) and glucose oxidase (GOD), respectively, for D‐fructose removal was constructed. Using this sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Li et al constructed a reaction purification system consisting of two continuously stirred tank reactors, which respectively contained immobilized glucose isomerase and glucose oxidase for the removal of d -fructose. In this system, d -fructose is converted to gluconic acid and is easily separated from d -allulose by anion exchange resins [ 139 ].…”
Section: Enzymatic Biotransformation Of D -Allulosementioning
confidence: 99%
“…Li et al constructed a reaction purification system consisting of two continuously stirred tank reactors, which respectively contained immobilized glucose isomerase and glucose oxidase for the removal of d -fructose. In this system, d -fructose is converted to gluconic acid and is easily separated from d -allulose by anion exchange resins [ 139 ].…”
Section: Enzymatic Biotransformation Of D -Allulosementioning
confidence: 99%
“…Further, the purity of D-allulose reaches 98.3% via an approach of DTF-Ca 2+ cation exchange chromatography (Xing et al, 2011). For the mixed system of D-allulose and D-fructose, D-fructose is first transformed into gluconic acid, and then D-allulose of 91.2% purity is obtained by anion exchange resin (Li et al, 2018b).…”
Section: Isolation and Purification Of D-allulosementioning
confidence: 99%
“…Enzymes that have been found to catalyze this reaction include d -tagatose 3-epimerase (DTEase) and d -allulose 3-epimerase (DPEase), of which DPEase appears to be superior to DTEase in terms of substrate specificity, but its poor thermostability limits DPEase application in d -allulose production . A few studies suggested that random and site-directed mutagenesis of DPEase might result in a modest improvement in thermal resistance. , Also, several attempts have been made to synthesize d -allulose from d -glucose through a two-step enzymatic cascade catalyzed successively by d -xylose isomerase and DTEase or DPEase. , Whether using d -fructose or d -glucose as a substrate, it generally requires immobilization as a way for stabilization and reuse of enzymes, as well as ion-exchange chromatography for separation of d -allulose from sugar mixtures …”
Section: Introductionmentioning
confidence: 99%
“…Also, there are more impurities contained in fermentation broth than in the enzymatic method. The generation of byproducts may further increase the difficulty of product separation. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation